A cost-sharing formula for online circulation and a union catalog through a regional, multitype library cooperative. - Arcari, R D (1987)
The experience of the Capitol Region Library Council and the University of Connecticut Health Center in developing a cost allocation formula for a circulation and online catalog shared by twenty-nine libraries is reviewed. The resulting formula identifies a basic unit cost as a minimum for each system participant.